Storage Behaviour onto Mint Oil: Physicochemical Properties - V. Shukla, Bhakti; M. Dixit, Chandra; Tiwari, Anuradha; K. Yadav, Sunil; K. Dixit, Arvind (Asian Journal of Chemistry, 2015)
In this study, the effect of storage conditions for the quality of mint oils was investigated. The changes in mint oil compositions were studied quarterly (each three months) during storage in different bottles for 12 months in the laboratory at room temperature (27 ± 3 °C) through stored upon the table, dark place (inside the shelf) and at low temperature (< 1 °C in a refrigerator). Optical rotation, refractive index and specific gravity have been investigated. The chemical properties of major constituents of Mentha arvensis oil were analyzed. The results demonstrate, for the storage of mint oils in the coloured glass bottles at cooling temperature.